Histomorphometrical and histochemical studies on the ovaries of domestic cat (Felis catus) - BANSAL, NEELAM; UPPAL, VARINDER; KUMAR, ASHWANI (The Indian Journal of Animal Sciences, 2011)
The study conducted on the ovaries of domestic cats revealed that the germinal epithelium of the ovaries varied from simple squamous to cubOIdal type. The tunica albuginea ovarii was made up of connective tissue fibres with abundant of collagen fibres. The number of primordial follicles was reported to be more as compared to primary, secondary and tertiary follicles. The increased size of corpus luteum may be due to the hypertrophy of large luteal cells. The activity of acid and neutral mucopolysaccharides and basic protein was strong in zona pellucida of ovarian follicles, whereas the sudanophihc lipid contents were more In the corpus luteum. The micrometrical observations showed that the average diameter offollicles varied from 38.89Â±7.79 Jlm in primordial follicle to 3026.30Â±9.85 11m in tertiary follicle. Â